Nearly non-magnetic valence band of the ferromagnetic semiconductor GaMnAs - Ohya, Shinobu; Takata, Kenta; Tanaka, Masaaki (Nature physics, 2011)
The origin of ferromagnetism in the prototype ferromagnetic semiconductor GaMnAs is controversial because of an insufficient understanding of its band structure and Fermi level position. This is a major issue for further development of this material for future semiconductor spintronics. Here, using a unique method combining a precise etching technique and resonant tunnelling spectroscopy, applied to a variety of surface GaMnAs layers, we can elucidate the universal valence-band (VB) picture of GaMnAs. We find that the VB structure of GaAs is almost perfectly maintained and does not merge with the impurity band for any of the GaMnAs samples, with Mn concentrations ranging from 6 to 15%, that we examined. Furthermore, the exchange splitting of the VB is found to be very small (only several millielectronvolts), even in GaMnAs with a high Curie temperature (154 K). Our findings shed light on the precise mechanism behind ferromagnetism in GaMnAs; a subject that has been debated for more than a decade. The magnetic properties of GaMnAs could be useful in the development of spintronic devices. Yet the precise origin of these properties has been hotly debated. Resonant-tunnelling spectra obtained from GaMnAs devices of superlative quality could finally resolve this issue.